Stress physiology of woody plants - Dai, Wenhao (Boca Raton, Florida : CRC Press, 2019)
This book addresses the importance woody plants have in agriculture, forestry, and the environment and how various stresses affect their performance. It reviews physiological and molecular responses of woody plants to major environmental stresses and focuses on the mechanisms involved in imparting resistance to stress. Chapters cover basics of plant physiology including plant structure and plant growth, photosynthesis, respiration, plant growth regulation, abiotic and biotic plant stresses including drought, water logging, nutrient deficiency, salinity, chilling, freezing, heat, oxidative stress, and heavy metal toxicity.
Woody plant structure -- Plant growth and development -- Photosynthesis and respiration in woody plants -- Plant growth regulation -- Plant response to drought stress -- Plant response to mineral nutrient deficiency -- Plant response to salinity stress -- Plant response to low temperature -- Plant response to oxidative stress -- Plants response to heavy metal stress -- Plant response to multiple stresses.
OCLC-licensed vendor bibliographic record.
Keywords: Woody plants -- Effect of stress on; NATURE / Plants / General; TECHNOLOGY / Agriculture / General; SCIENCE / Life Sciences / Botany